Garasi rumah berbasis internet of things - Santoso, Nurul Adi; -, Sujono (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
To make it easier for humans in everyday life, many inventors make tools that will make human life easier. Smart Garage is one of the inventions that can make it easier for users in everyday life. When users want to enter the garage, they don't need to get out of the car, because they only need to press their Smartphone. The working principle of the Smart Garage is connected to the NODEMCU (Node Micro Controller Unit) circuit. The motor circuit for the door is a Servo which is connected to the NodeMCU which will later recognize the commands sent via the Smartpone. This tool is made with the aim of making it easier for us in daily activities, without having to push / pull the garage door. With this, the garage door can be opened and closed by a command controlled by humans as users. The conclusion of all projects that are made is in order to meet the specifications that have been planned by the author in terms of software and hardware.